Handbook of entrepreneurship and co-operative development - Hassan Ali; Chandrakantan Subramaniam (Co-operative and Entrepreneurship Development Institute (CEDI), 2013)
The purpose of this Handbook of Entrepreneurship Co-operative Development is to provide an overview of the key issues in entrepreneur ship and co-operative research